STRA13 expression and subcellular localisation in normal and tumour tissues: implications for use as a diagnostic and differentiation marker. Issue 7 (1st July 2005) - Ivanova, A; Liao, S-Y; Lerman, M I; Ivanov, S; Stanbridge, E J
Abstract : Background: STRA13 is a bHLH transcription factor that plays a crucial role in cell differentiation, proliferation, apoptosis, and response to hypoxia. Objective: To assess STRA13 involvement in carcinogenesis and evaluate its diagnostic value. Methods: A comprehensive analysis was undertaken of the endogenous protein expression in 389 normal and corresponding malignant specimens, using newly generated polyclonal antibodies. Results: STRA13 was commonly expressed in epithelial cells of normal and neoplastic tissues where it was confined mostly to the nucleus. Intense cytoplasmic STRA13 immunoreactivity was characteristic of myoepithelial and differentiated squamous epithelial cells of all organ sites and their neoplastic counterparts, suggesting application of STRA13 as a myoepithelial cell marker. A distinctive apical granular cytoplasmic staining pattern observed in the pancreas and large intestine was retained in corresponding metastatic carcinomas, providing for identification of the primary sites of these disseminating tumours. In less differentiated tumours there was a tendency to lose the cytoplasmic staining or to switch to nuclear STRA13 staining. Analysis of STRA13, HIF-1α, and CAIX expression patterns in a large set of various tumours substantiated the association of STRA13 with HIF-1α expression and hypoxia in vivo. Investigation of the molecular mechanisms of STRA13 nucleo-cytoplasmic shuttling suggested that STRA13 employs nuclear import/export that utilises the NLS/NES motifs situated within the N-terminus and in the middle of the protein. Conclusions: STRA13 may serve as a marker for myoepithelial cells, for the degree of tumour differentiation, and for identification of the primary site of certain metastatic tumours. In combination with CAIX and CAXII markers, it may lead to a more accurate classification of all renal carcinomas.